Gastroprotective and anti-inflammatory activities of a mixture of Melastoma malabathricum L. and Muntingia calabura L. leaves - Halim, Siti Zawanah (2017)
Gastric ulcer is a part of the peptic ulcer disease which well acknowledged as one of major human illness. Basically, the gastric ulcer is occurred due to the imbalance between the protective factors and aggressive factors in the stomach. Recently, there were a few of medicines being used to treat the gastric ulcer. However, those medicines had caused certain adverse effects. At the same time, medicinal plants have proved to give positive results as the treatment for many diseases including gastric ulcer. Melastoma malabathricum (MM) and Muntingia calabura (MC) were two plants which have been studied for their pharmacological activities. In addition, the previous study had also reported the markedly gastro protective effect of both those plants leaves individually via in vitro and in vivo experiments. Thus, in attempt to develop a pharmaceutical product with antiulcer potential, it is necessary to make sure it is effective at lower dose range, so the present study was aimed to identify the gastroprotective activity of methanol extract of a mixture of Melastoma malabathricum and Muntingia calabura(MMMC) at various ratio using rats models and further investigate whether combination of those plant at various ratio will exert synergistic effect by enhancing or reducing the observed antiulcer activity. The small particle of MM and MC grinded leaves were mixed together based on three different ratios (1:1, 1:3 and 3:1; w/w) and soaked in methanol in ratio 1:20 for 72 hours, filtered and evaporated using the rotatory evaporator to get the concentrated crude extract. By using the crude extract obtained from the evaporation process, the doses (15, 150 or 300 mg/kg) were prepared. Ranitidine (100 mg/kg) was used as a reference drug while 2% Tween 80 was used as a negative control. The Sprague-Dawley rats were given the test solutions orally for seven consecutive days and were subjected to the ethanol-induced gastric ulcer. The rats were euthanized; macroscopic and histological observations of the gaster were done. The ulcer area (UA) was determined and the percentage of the inhibition exhibited by the MMMC was calculated. The gaster was subjected to antioxidant studies including the superoxide dismutase (SOD), catalase (CAT), glutathione (GSH), prostaglandin E2 (PGE2) and malondialdehyde (MDA) assay. The MMMC was tested for antioxidant study using the total phenolic content (TPC), oxygen radical absorbance capacity assay (ORAC) and 2,2- diphenyl-1-picrylhydrazyl radical scavenging assay (DPPH). The antisecretory potential of MMMC was investigated using the pyloric ligation model while the role of nitric oxide and endogenous sulfhydryl group were measured by testing the extract against L-NG-Nitroarginine Methyl Ester (L-NAME) and N-Ethylmaleimide (NEM)using the ethanol-induced model. Ratio 1:1 of MMMC showed the most effective gastro protective activity in which it significantly (P<0.05) reduced the gastric lesion when assessed using the ethanol-induced gastric ulcer models. The macroscopic findings were validated by the microscopic observations. Furthermore, except for the pH and total acidity, the extract also significantly (P<0.05) reduced the volume of gastric content whereas the mucus content was significantly (P<0.05) increased in MMMC-treated rats in the pyloric-ligation test, where by ratio 1:1 constantly exhibited the best result among the three ratios. Besides that, the gastro protection effect of MMMC significantly (P<0.05) involved the participation of nitric oxide and sulfhydryl compounds. Ratio 1:1 of MMMC showed the highest value of TPC and ORAC activity compared to the other ratios, meanwhile ratio 3:1of MMM Cexhibited the strongest IC50of DPPH scavenging activity. The in-vitro anti-inflammatory effect of MMMC evaluation showed moderate NO inhibitory activity at IC50ofratio 1:1 and 1:3 of MMMC, compared to ratio 3:1 which showed weak NO inhibitory activity. While the antioxidants studies of the stomach revealed the improvement of CAT, SOD, GSH, PGE2 and MDA activities by MMMC with ratio 1:1 showed the best result among the three ratios. Besides that, the result obtained from the GC-MS analysis showed several peaks detected at the different real time suggested that MMMC contained several compounds that have been proven by other studies to show antioxidant, anti-inflammatory and gastro protective effect. The UHPLC analysis suggested that the presence of quercetin and gallic acidin the most effective ratio of MMMC, which is 1:1 was confirmed in MMMC. In conclusion, MMMC at the ratio of 1:1, exerted the best gastro protective activity against the ethanol-induced gastric ulcer assay partly by activating its antisecretory and antioxidant activities, together with modulation of the gastric tissue endogenous antioxidant system.